PROBLEMATIKA IHDAD DAN DINAMIKA PEMIKIRAN HUKUM ISLAM DI INDONESIA - Zaiyadi, Ahmad; Abdi, Efan Chairul (As-Syifa: Journal of Islamic Studies and History, 2022)
On the one hand, ihdad demands that it be understood more textually on the mainstream, while on the social demands it demands equality, demands for human rights and so on. Especially in Indonesia, the view of ihdad between traditional and liberal in responding to the issue of reforming Islamic law in Indonesia occurs dialectically in that discourse. Therefore, it is important to conduct further research on Ihdad focused on both views, intending to analyze the opinions of Liberalism and Traditionalism against Ihdad and its relevance to Islamic law reform in Indonesia by using the method of literature studies based on a comparative approach. This study concludes that the liberalist view of ihdad looks at all aspects, including looking at the context of Arab civilization at that time, then compared it with the context of the society in different places and times. Therefore they put Ihdad's problem in a condition that would happen to humans even without any conditioning demands from the legal aspect. Meanwhile, traditional figures formulate the concept of ihdad in the same way as the opinion of the priests of the four madhhabs or classical fiqh, namely placing the problem of Ihdad in mandatory law and determining the conditions in ihdad. By looking at the characteristics of the two ideas above, what is relevant is the model of moderate thought between the two which is more directed at developing the subject of Ihdad law which is not only limited to the wife but also to the husband after first determining the reason for Ihdad, namely to mourn and avoid slander. Then, the provision of time in performing Ihdad must be adjusted to the situation